Corporate Social Responsibility in Family Business: A Scoping Literature Review - Fitriya Andriyani; Sulis Rochayatun (Institut Agama Islam Negeri Kendari, 2022)
The study of Corporate Social Responsibility (CSR) is a phenomenon that continues to grow in the business world, which was initially widely studied in large companies and then developed in the study of family companies. Therefore, the literature on the topic must provide an updated overview of CSR research. This literature aims to study the concept of corporate social responsibility in family firms. This literature review follows the guidelines of (Arksey & O'Malley, 2005), which have five steps: identifying the research questions; identifying relevant studies; selecting studies; charting data; reporting, summarising, and reporting the results. The study was derived from the electronic database of Emerald, Springer, and Taylor Francis. Results show that corporate social responsibility in family companies is sustainable and a form of building reputation, family identity, and a good image in the business environment. The implications of this study are expected to be a reference and guide for implementing CSR in the family business to benefit wider stakeholders.